Nushus al–Waridah Fil Miqdar al–Muharram Minarridha’: Dirasah Tahliliah - Naamane Djeghim (State of Islamic Institute Langsa, 2020)
This study explaines about views of Muslim jurists on the amount of breast milk that establishes fosterage and prohibits marriage based on the differences in the relevant legal texts. This research, critically, examines those texts, especially those that require five counts of breastfeeding. The methodology is based on critical examination of all the texts to establish their authenticity and relevance. The Researcher argued For safety, it is recommended to consider any amount of breastfeeding as a cause of fostering and prohibition. It concluded that there is doubt about the authenticity of those texts require five counts of breastfeeding.